Analysis of Connecting Rod Based on Finite Eliment Approach - M. M., Noor; K., Kadirgama; Julie J., Mohamed; M. R. M., Rejab (2008)
The connecting rod is one of the most important pats of an automotive engine. The connecting rod is subjected to a complex state of loading. High compressive and tensile loads are due to the combustion and connecting rod’s mass of inertia respectively. The connecting rod fails during the operation of the engine is the critical situation. Therefore the connecting rod should be able to withstand tremendous load and transmit a great deal of power smoothly. The objective of this paper is to investigate the failure analysis of the connecting rod of the automotive engine. The materials including carbon steel, mild steel, bass and aluminum are considered in this study. The linear static analysis was carried out utilizing the finite element analysis codes. The numerical results were verified with the experimental results. It can be seen from the acquired results that the carbon steel gives good results in terms of hardness and endurance limit compared with the other materials.